ANALISIS PENGARUH NILAI TUKAR DAN INFLASI TERHADAP NERACA PERDAGANGAN DI INDONESIA 2008 – 2018 - Nancy Sitompul; Maria Siahaan (LPPM Universitas HKBP Nommensen, 2020)
Indonesia’s trade balance records the export and import of goods carried out by the Indonesian State. Indonesian trade balance movement. The trade balance can be called net exports. The results of this study can rate index have also be seen that inflation and the exchange rate index have a significant impact on changesin the trade balance for 2008 to 2018. The appreciated Rupiah (an increase in the value of the currency) will have an impact on the competitiveness of domestic goods on the international market so that the balance sheet have improved. Meanwhile, if there is an increase in the inflation rate, it indicates the value of domestic commodity prices and exporters’interest in domestic goods will decline, so this will cause exports to fall and will later have an impact on the surplus of the balance sheet.